Sintonización de ecualizadores difusos basada en técnicas de agrupamiento y mapas autoorganizados - Figueroa R, John A; Corrales C., Diego A. (Ingeniería, 2005)
This paper present two novel algorithms for tuning second order fuzzy equalizers. The algorithms are based on data clustering and selforganizing maps techniques. In addition, this paper presents some experimental results concerning the behavior of both algorithms when the parameters of the channel vary.